A Scarcity of Biospheric Values in Local and Regional Reporting of Water Issues: Media Coverage in the Floridan Aquifer Region - Sadie Hundemer; Debbie Treise; Martha Monroe (Journal of Applied Communications, 2022)
The values invoked by journalists in the reporting of water issues influence public support for water policy and the assessment of water tradeoffs. This qualitative framing analysis of water coverage from six newspapers in the Floridan aquifer region from 2010 to 2018 reveals the values used to stimulate reader engagement on a range of water challenges including weather, residential behavior, agriculture, algae, industry, springs, energy, municipalities, and fecal matter. Results reveal a hierarchy of value frames that prioritizes economics and human health, thereby attending primarily to the motivations of egoistic and social-altruistic individuals. The ecosystem implications of deteriorated water conditions, which are of particular interest to biospherically-oriented individuals, received relatively little journalistic attention. This finding suggests that the framing of regional water issues could unintentionally affect reader interest, public prioritization of social goods, and policy interventions.
Keywords: framing; water; priming; values; agenda setting